Three dimensional numerical study of PV module cooling by using thermoelectric effects and nano-enhanced confined multiple slot jet impingement - Selimefendigil, Fatih; Okulu, Damla; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2024)
In this study, 3D numerical study of photovoltaic (PV) module cooling is analyzed by combined utilization of thermoelectric generator (TEG) and nano-enhanced slot jet impingement system. For the relevant parameters of interest, such as Reynolds number (between 10 and 100), nanoparticle loading (solid volume fraction between 0 and 0.02), non-dimensional vertical distance between the slots and upper plate (between 2.5 and 8), non-dimensional spacing between the slots (between 2.5 and 8), and cold NF inlet temperature (between 20oC and 30oC), finite element method is utilized. Using only TEG and nano-jet assisted cooling with TEG result in PV -cell temperature reduction by about 43.33oC and 69.55oC as compared to un-cooled PV module. It is observed that cell temperature decreases by about 2.4oC-2.9oC when considering the minimum and maximum Reynolds number cases. When nanoparticle loading is increased to 0.02, output TEG power rises while cell temperature decreases by about 0.75oC. When varying the vertical distance between the slot to the impinging surface, cell temperature changes up to 1.9oC while distance between the slots has very slight impact on the temperature variation. Decreasing the inlet fluid temperature by about 10oC decreases the cell temperature by about 8.5oC.
Keywords: PV cooling; Jet impingement; Hybrid nanofluid; Thermoelectric; PV module; Finite element method